An integrated system for image processing - Delrieux, Claudio (2002)
In this work we present an integrated image processing system PDICalc, which is a simple but powerful combination of image processing technologies with a spreadsheet user interface. Our system enables users to build an image processing pipeline, considering each step separately, and visualizing the results of modifying the parameters of each step in the final image. A spreadsheet based user interface eliminates the tedious and repetitive interaction that characterizes current image processing software. Users can build a processing template and reliably repeat processing steps without the effort of redevelopment or recoding. This template can be then reused with any input image, can be stored for future processing sessions, and every step can be trimmed precisely to achieve the desired results. We develop several examples of complex processing tasks (character segmentation, spectral masking, and thematic map imaging) where we show how easy and flexible is to develop a processing pipeline with our system.